2017
DOI: 10.1159/000484950
|View full text |Cite
|
Sign up to set email alerts
|

Association between Loss of Skeletal Muscle Mass and Mortality and Tumor Recurrence in Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Background: Hepatocellular carcinoma (HCC) has multiple prognostic factors, and there is an increase in knowledge about the body composition and physical status of patients with HCC. The present meta-analysis aimed to explore whether loss of skeletal muscle mass is associated with mortality and tumor recurrence in patients with HCC. Method: A systematic search was conducted for published literature using PubMed, Embase, and Scopus. We included cohort or case-control studies investigating patients with HCC. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
153
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 41 publications
4
153
3
1
Order By: Relevance
“…Moreover, it has been reported that MVL is a more significant prognostic factor than portal hypertension in liver cirrhosis (LC) patients (Child‐Pugh class A/B), and also an important prognostic factor following not only surgical resection but also SOR treatment in patients with HCC. Recently, a meta‐analysis study reported that MVL was a prognostic factor regardless of therapeutic modality given for HCC by Chang et al Furthermore, in addition to LC and HCC, muscle volume has been reported to be an important prognostic factor in patients receiving treatments for other types of cancers . In the present study, a fair percentage of our patients (35.3%) had MVL and a relative decline in muscle volume at 4 and 12 weeks after starting LEN was observed in patients who had data of CT imaging findings available, similar to our past study of patients treated with SOR .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, it has been reported that MVL is a more significant prognostic factor than portal hypertension in liver cirrhosis (LC) patients (Child‐Pugh class A/B), and also an important prognostic factor following not only surgical resection but also SOR treatment in patients with HCC. Recently, a meta‐analysis study reported that MVL was a prognostic factor regardless of therapeutic modality given for HCC by Chang et al Furthermore, in addition to LC and HCC, muscle volume has been reported to be an important prognostic factor in patients receiving treatments for other types of cancers . In the present study, a fair percentage of our patients (35.3%) had MVL and a relative decline in muscle volume at 4 and 12 weeks after starting LEN was observed in patients who had data of CT imaging findings available, similar to our past study of patients treated with SOR .…”
Section: Discussionsupporting
confidence: 88%
“…38 Moreover, it has been reported that MVL is a more significant prognostic factor than portal hypertension in liver cirrhosis (LC) patients (Child-Pugh class A/B), 39 and also an important prognostic factor following not only surgical resection 40 but also SOR treatment 41 in patients with HCC. Recently, a metaanalysis study reported that MVL was a prognostic factor regardless of therapeutic modality given for HCC by Chang et al 42 Furthermore, in addition to LC and HCC, muscle volume has been reported to be an important prognostic factor in patients receiving treatments for other types of F I G U R E 5 Hand-foot skin reaction occurrence in tyrosine kinase inhibitor-experienced group. Of 8 patients who had undergone past tyrosine kinase inhibitor (TKI) treatments and developed a grade 3 hand-foot skin reaction (HFSR), 87.5% had an HFSR with lenvatinib (LEN) therapy (G3, 2, 1; n = 2, 3, 2, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is associated with unfavorable mortality in patients with cirrhosis or HCC, independent of liver function reserves . Patients with HCC receive various treatments along with assessments of both TNM stage and liver function reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HCC are treated by various methods based on HCC stage and degree of liver damage before treatment. Sarcopenia has a negative impact on patients with HCC treated with surgical resection, locational therapies, and sorafenib . Transcatheter arterial chemoembolization (TACE) is standard therapy for patients with intermediate‐stage HCC .…”
Section: Introductionmentioning
confidence: 99%
“…For the longest time, the frailty and pronounced muscle weakness that characterizes the majority of HCC patients received much less attention. This has significantly changed in recent years as reports were published from independent groups about the important role of sarcopenia and cachexia in predicting both clinical course and response to therapy of HCC patients . Cachexia is widely considered to be a multifactorial syndrome with various manifestations throughout the whole body.…”
Section: Discussionmentioning
confidence: 99%